Management Education (DSME) Diabetes through the Whatsapp Application in Diabetes Mellitus Type II Clients - Yustina Dwi Cahyanti; Nina Indriyawati; Shobirun Shobirun (Poltekkes Kemenkes Semarang, 2020)
Background: Diabetes Mellitus (DM) is a chronic metabolic disease that requires self-management education to prevent complications. Diabetes Self Management Education (DSME) is used as an effective method in improving the independent care of DM patients when discharged from the hospital. There are still many methods of delivering health education in several hospitals using poster / leaflet print media that are placed in strategic locations. Another method that can be done is to use the WhatsApp application.Purpose: This study aims to determine the feasibility of health education media about DSME through the WhatsApp application on Diabetes Mellitus type II clients.Methods: The method in this study uses Research and Development (RD) by using the ADDIE model development method (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were conducted by 3 experts (health promotion experts, nursing practitioners, and surgical medical nurses) and 10 clients with type II DM. In this study using a validation sheet from 3 experts by providing an assessment of the media used by researchers includes 3 aspects, including: aspects of the material, aspects of the content, and aspects of appearance.Results: The internal validity test was carried out by 3 experts with an average percentage rating on the material aspect of 93.3%, the content aspect of 95% and the display aspect of 91.6%. External validity test results obtained from trials limited to 10 clients with an average percentage of results in 3 aspects, among others: 96.5% material aspects, 95.5% understanding aspects and 96% display aspects.Conclusion: Submission of DSME through the WhatsApp application is considered very feasible to be used as a medium for delivering material for type II DM clients because it can improve understanding of self-management when discharged from the hospital.